Physical Activity Guidelines for Chinese (2021) - Composing and Editorial Board of Physical Activity Guidelines for Chinese (Editorial Office of Chinese Journal of Public Health, 2022)
The Physical Activity Guidelines for Chinese (2021) is composed of seven parts, including the general guidelines, children aged 2 years and below, children aged 3 - 5 years, children and adolescents aged 6 - 17 years, adults aged 18 - 64 years, the elderly aged 65 years and above, and patients with chronic diseases. The guidelines was compiled by the Composing and Editorial Board organized by Chinese Center for Disease Control and Prevention and China Institute of Sport Science. The compilation of the guidelines was directed by the Bureau for Diseases Prevention and Control of the National Health Commission of the People's Republic of China.